Medical Students\' Attitude Towards Research at the Completion of Basic Science Courses - Nooshin Mirkheshti; Naeimeh Hoseini; Mohammad Khaloei; Arash Hadadgar (مجله ایرانی آموزش در علوم پزشکی, 2014)
Introduction: Assessing the attitude of medical students who has passed basic sciences, toward research and research activities in basic sciences, can provide a powerful basis for future interventions and improvement in their attitudes. In this study in Isfahan Medical School, the attitude of newcomer medical students toward research and specially research in basic sciences has been investigated at the completion of physiopathology courses.Methods: This is a descriptive cross-sectional study performed on all newcomer medical ‎students in physiopathology course after basic science courses in Isfahan ‎University of Medical Sciences in year 2010 (n=65). The instrument was a researcher made ‎questionnaire including 33 questions. The questionnaire was validated through face and content validity and its reliability was confirmed based on Cronbach’s Alpha (0.85). We used student T-test, Spearman and Pearson correlation coefficient for statistical analysis.Results: The mean of research understanding was 5.9± 1.49 out of eight. There was a significant positive relationship between previous research activities and the score of research understanding. There was also a significant relationship between interest toward research and doing research in clinical fields among students interested in research activities.Conclusion: Students showed a positive attitude toward research. However, they were more interested in clinical research rather than basic research and most students interested in research activities preferred clinical studies as their future activities. Offering MD-PhD dual degree training programs and recruiting physician scientist in them could introduce some career opportunities in this field and also train the demanding researchers for research centers in Iran medical research centers.